An analysis of the timeout in water polo games - Suga, M. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
The timeout rule has been applied in water polo games since 1996. This research was conducted to consider the way to request a timeout effectively in water polo games. A total of 248 timeout situations were collected from the official score sheets of the World Championship (at Perth in '98) and the Universiade (at Cicilia in '97).The findings on this study are as follows:1) Many of the timeouts were requested in the fourth period of the games. To be more specific, 126 timeouts (50.8%) occurred in the last four minutes of the fourth period.2) 139 timeouts (56.0%) were requested with a score difference of two points and less.3) The situations where a timeout was requested were after the award of a free throw by exclusion fouls (50.0%), during possessing the ball (41.1%), and restarting after a goal (8.1%).4) The immediate effects of 102 timeouts (41.1%) were scoring a goal and gaining exclusion fouls from opponents.5) The time and situation where a timeout was requested were classified into six patterns (see Fig.1): [a] a closing phase at the end of the game, [b] a closing phase at the start and in the middle of the game, [c] a phase with the possibility of a turnaround, [d] a final phase in the lead, [e] a phase with certainty of victory, and [f] a phase with certainty of defeat.